Application of Artificial Intelligence (AI) Technologies to Accelerate Market Segmentation - Mandapuram, Mounika; Gutlapalli, Sai Srujan; Reddy, Manjunath; Bodepudi, Anusha (Global Disclosure of Economics and Business, 2020)
In recent years, rapid advancements have been made in information technology, processing power, data handling systems, robotics, and artificial intelligence. These advancements have been made possible by recent developments in robotics. As a result of its tremendous potential and usefulness, it is currently being utilized in a wide variety of industries, including information technology, the retail sector, space science, the automotive industry, the entertainment industry, medical, transportation, medical, social sciences, and business management, amongst others. This article focuses on the exciting connotation between market segmentation and artificial intelligence (AI), which has emerged due to recent developments in the industry. Even while the propositions are being made, the ways of AI engagement in developing applications are being developed. Digital marketing, a legitimate application of marketing science, has successfully boosted customer engagement and provided value for businesses. This is performed by utilizing various digital and electronic services. In this article, we will discuss what artificial intelligence (AI) is and how recent AI breakthroughs influence the expansion and development of market segmentation. In addition, this article explores how the activities and functions of sales and marketing are affected by the various AI techniques and methodologies currently available.